Examination of CO2 emission of different stubbles on a chernozem soil - Kovács, Györgyi (Acta Agraria Debreceniensis, 2010)
Applying alternative soil cultivation methods based on reduced disturbance of the soil more favourable conditions can be created in order to increase the organic matter content of the soil and the availability of the nutrients for the crops. In complex soil tillage experiment – in 1997 was set on – at Karcag, as the element of the investigation of soil reduced and conventional tillage systems. There is close correlation between the degree and intensity of CO2-emission from the soil and the structural state and organic matter content of the soil. In order to quantify the increased CO2-emission from soil due to soil preserving cultivation systems, in situ CO2-emission of soil was measured by means of an ANAGAS 98 infrared gas analyser. The soil type of the investigated plot is meadow chernozem solonetz in the deeper layers, a soil type that is characteristicfor the Trans-Tisza Region of Hungary. In this paper the results gained from the measurement on different stubbles are published, as we consider stubbles the most suitable state when the effects of different soil cultivation systems on the microbiological activity of the soil can be compared. Experimental data provided information about the length of the time period when CO2 emission increasing effects of soil cultivation are observable. Studying the effect of different soil cultivation methods on the CO2 emission from chernozem soil is indisputably actual and needs more efforts as it can contribute to develop a more environmental friendly agricultural production. The main goal of these measurements was to determine the effect of soil cultivation technologies and certain agrotechnical elements on the factors of the soil carbon cycle.